Vietnam Defense Strategy in Dealing with The South China Sea Conflict - Tri Hadinata; Rudy Susanto; Lukman Yudho Prakoso (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Vietnam is a country in Southeast Asia located on the Indochina Peninsula. The country has the full name of the Socialist Republic of Vietnam and is a communist state that recognizes one party, the Communist Party. Vietnam's involvement in the South China Sea conflict has national interests as the basis for fighting over the territory. The South China Sea is currently in the spotlight because of the disputes there. The geographic location of Vietnam is at 80 North Latitude-240 North Latitude and 1020 East Longitude – 1100 East Longitude, with an area of ​​331,210 km2. The method used in this article is descriptive qualitative, in this article explaining Vietnam's sea defense strategy. Vietnam has a fleet of 9 frigates, 14 corvettes, 45 Paroli ships, 6 submarines and 8 warships. Based on this information, Vietnam's marine defense system is included in the Green Water Navy group. Then the potential threat of the South China Sea dispute that might occur was also brought to the ASEAN Forum to get support from ASEAN member countries. We can take the lesson that a country whose sovereignty is threatened will definitely make preparations and anticipate in carrying out defense and defense by strengthening its combat fleets.